Research of Aphorisms in World Linguistics - Tashpulatova Dilnoza Xolmirza qizi (Zien Journals, 2022)
Aphorisms have always attracted people's attention, but in the current era, in the era of scientific and technical progress, their importance is especially increasing; It is no coincidence that aphorism is actively developing in a number of countries and has reached its peak in some places. The problems of aphoristics are discussed at literary conferences and many studies are devoted to them. This article explains research of aphorisms in world linguistics and their origin. Moreover, scientists who worked about meaning of aphorisms in different countries from ancient till now.
Keywords: Aphorism; ethics; philosophy; proverb